Poly(Styrene-Divinyl Benzene)-Based Monolithic Column For High Performance Liquid Chromatography - Abd. Aziz, Norsyariza; Abu Naim, Ahmedy; Sanagi, Mohd. Marsin; Wan Ibrahim, Wan Aini (SPS, UTM, 2006)

(untitled)
Poly(styrene-divinyl benzene) (PS-DVB) monoliths were synthesized by in-situ polymerization in a 2.1 mm Ã— 150 mm high performance liquid chromatography, (HPLC) column. The physical properties ofthe monolith were studied by FTIR and SEM. IR spectra of the monolith confirmed the formation of PS-DVB whereas SEM analysis shows that the PS-DVB monolith gave the cauliflower structure. The performance of the synthesized column was evaluated by HPLC and compared with commercial PS-DVB column. The separations were carried out using 4 test compounds; benzaldehyde, nitrobenzene,phenol and toluene. Although the monolith column was less efficient than commercial packed PS-DVB column, the monolith gives faster analysis time.